2017
DOI: 10.1093/chemse/bjx005
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pregnancy on Taste Function

Abstract: It is common for women to report a change in taste (for instance an increased bitter or decreased sweet response) during pregnancy, however specifics of any variation in taste with pregnancy remain elusive. Here we review studies of taste in pregnancy, and discuss how physiological changes occurring during pregnancy may influence taste signaling. We aim to consolidate studies of human pregnancy and "taste function" (studies of taste thresholds, discrimination, and intensity perception, rather than hedonic resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
1
20
0
3
Order By: Relevance
“…In pregnancy, many physiological changes take place and a change in taste is one of them. [6][7] This is confirmed in this present study where 30% of the pregnant women experienced change in taste. About 40% of the pregnant women have specific taste preference while only 22% of them detest particular taste.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In pregnancy, many physiological changes take place and a change in taste is one of them. [6][7] This is confirmed in this present study where 30% of the pregnant women experienced change in taste. About 40% of the pregnant women have specific taste preference while only 22% of them detest particular taste.…”
Section: Discussionsupporting
confidence: 89%
“…23 A change in taste sensitivity has been reported in similar studies on pregnant women. 6,7,24,25 The taste detection threshold of pregnant women was significantly lower when compared to nonpregnant women (P ¼ .002 or Table 2). Decrease in a particular taste sensitivity or detection threshold will make the individuals to add supplements that will improve the missing taste to their food so as to have savory meals.…”
Section: Discussionmentioning
confidence: 97%
“…Regardless, sex differences are regularly observed in taste (3,11,45,46), although many studies lack an assessment of umami (10,11,47). Circulating sex hormones such as estrogen have been hypothesized to differentially influence taste perception between sexes (46), particularly during pregnancy and certain phases of the menstrual cycle (48,49). Despite this, baseline and post-treatment testing sessions were separated by 28 days, the approximate length of a typical menstrual cycle (50), limiting any effect of menstrual cycle on taste.…”
Section: Perceived Umami Intensity After a Diet High In Msgmentioning
confidence: 99%
“…It has reported that sweetness susceptibility changes in older 1) , and stressed conditions 2) . It also reported that sweets may be eaten too much during pregnancy 3) and quit smoking 4,5) . It also reported that the threshold for sweetness may increase by eating a lot of sweets during childhood when the taste is created 6,7,8) .…”
Section: Discussionmentioning
confidence: 99%